PENYULUHAN KESEHATAN MENGENAI PERILAKU HIIDUP BERSIH DAN SEHAT (PHBS) PADA ANAK USIA SEKOLAH DI DESA BINUANG KECAMATAN BANGKINANG - Ade Dita Puteri; Devina Yuristin (Universitas Pahlawan Tuanku Tambusai, 2021)
Healthy behavior and the ability of the community to choose and obtain quality health services greatly determine the success of health development, therefore one of the main health efforts or the mission of the health sector is to encourage community independence to live healthy. School age children are a critical age group, because at that age a child is vulnerable to health problems. Apart from being prone to health problems, school-age children are also very sensitive to stimuli so that they can be easily guided, directed and inculcated in good habits, including habits of having a clean and healthy lifestyle. The community service activity in Binuang Village, Bangkinang Subdistrict, Kampar Regency, entitled